2023
DOI: 10.1177/09636897231173736
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes From Adipose-Derived Stem Cells Suppress the Progression of Chronic Endometritis

Bin Wang,
Li Li,
Ruizhu Yu

Abstract: Chronic endometritis (CE) is closely linked to the reproductive failure. Exosome (Exo)-based therapy is proposed as an encouraging strategy in inflammation-related disorders; however, little work has been devoted to its usage in CE therapy. An in vitro CE was established by administration of lipopolysaccharide (LPS) in human endometrial stromal cells (HESCs). The cell proliferation, cell apoptosis, and inflammatory cytokine assays were performed in vitro, and the efficacy of Exos derived from adipose tissue–de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…However, IFN-γ suppressed miR-221 [117]. In addition, exosomes enriched in miR-21 exerted an anti-inflammatory effect by blocking TLR4 and NF-kB signaling pathways [118]. However, miR-21 was downregulated by high glucose in diabetic patients [119].…”
Section: Aging and Metabolic Reprogramming Decrease The Number And Fu...mentioning
confidence: 98%
“…However, IFN-γ suppressed miR-221 [117]. In addition, exosomes enriched in miR-21 exerted an anti-inflammatory effect by blocking TLR4 and NF-kB signaling pathways [118]. However, miR-21 was downregulated by high glucose in diabetic patients [119].…”
Section: Aging and Metabolic Reprogramming Decrease The Number And Fu...mentioning
confidence: 98%
“…Research has shown that miR-21 expression is considerably downregulated following an LPS challenge, suggesting that miR-21 is involved in the endometrial inflammatory response ( Ibrahim et al., 2019 ). In recent study, it was also shown that exposure to LPS decreased miR-21 levels in hESCs, while administration of AD-MSCs-derived exosomes resulted in increased miR-21 expression ( Wang et al., 2023 ). Based on reports, overexpression of miR-21 inactivates TLR4/NF-kB pathway by downregulation of TLR4 expression ( Liu X-J.…”
Section: Exosomes-tlrs Intraction and Infection Controlmentioning
confidence: 99%
“…Also, a study performed by Wang et al. showed that exosomes from AD-MSCs can suppress the progression of chronic endometritis (CE) ( Wang et al., 2023 ). For this purpose, human endometrial stromal cells (hESCs) were used to create an in vitro CE and a mouse model with LPS-induced CE in vivo was used to assess the effectiveness of Exos derived from AD-MSCs in vivo ( Wang et al., 2023 ).…”
Section: Exosomes-tlrs Intraction and Infection Controlmentioning
confidence: 99%
See 2 more Smart Citations